The prognosis of N2b and N2c lymph node disease in oral squamous cell carcinoma is determined by the number of metastatic lymph nodes rather than laterality: Evidence to support a revision of the American Joint Committee on Cancer staging system - Ardalan Ebrahimi; Ziv Gil; Moran Amit; Tzu‐Chen Yen; Chun‐Ta Liao; Pankaj Chaturvedi; Jai Prakash Agarwal; Luiz Paulo Kowalski; Hugo Fontan Köhler; Matthias Kreppel; Cláudio Roberto Cernea; José Brandão; et al. (2014)
BACKGROUND A study was conducted to assess for prognostic heterogeneity within the N2b and N2c classifications for oral cancer based on the number of metastatic lymph nodes and to determine whether laterality of neck disease provides additional prognostic information. METHODS An international multicenter study of 3704 patients with oral cancer undergoing surgery with curative intent was performed. The endpoints of interest were disease‐specific survival and overall survival. Model fit was assessed by the Akaike Information Criterion and comparison of models with and without the covariate of interest using a likelihood ratio test. RESULTS The median number of metastatic lymph nodes was significantly higher in patients with N2c disease compared to those with N2b disease ( P < .001). In multivariable analyses stratified by study center, the addition of the number of metastatic lymph nodes improved model fit beyond existing N classification. Next, the authors confirmed significant heterogeneity in prognosis based on the number of metastatic lymph nodes (≤ 2, 3‐4, and ≥ 5) in patients with both N2b and N2c disease ( P < .001). A proposed reclassification combining N2b and N2c disease based on the number of metastatic lymph nodes demonstrated significant improvement in prognostic accuracy compared with the American Joint Committee on Cancer staging system, and no improvement was noted with the addition of a covariate for contralateral or bilateral neck disease ( P = .472). CONCLUSIONS The prognosis of patients with oral cancer with N2b and N2c disease appears to be similar after adequate adjustment for the burden of lymph node metastases, irrespective of laterality. Based on this finding, the authors propose a modified lymph node staging system that requires external validation before implementation in clinical practice. Cancer 2014;120:1968–1974 . © 2014 American Cancer Society .